2017
DOI: 10.1016/j.micres.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc solubilizing Bacillus spp. potential candidates for biofortification in maize

Abstract: Bioaugmentation of Zn solubilizing rhizobacteria could be a sustainable intervention to increase bioavailability of Zn in soil which can be helpful in mitigation of yield loss and malnutrition of zinc. In present study, a number of pure rhizobacterial colonies were isolated from maize rhizosphere and screened for their ability to solubilize zinc oxide. These isolates were screened on the basis of zinc and phosphate solubilization, IAA production, protease production, catalase activity and starch hydrolysis. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
146
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(173 citation statements)
references
References 38 publications
25
146
1
1
Order By: Relevance
“…A total of 25 isolates from C. brasiliensis tissues and the rhizosphere presented ability to solubilize zinc in the qualitative test, of which eight presented halo diameters greater than or equal to 13 mm. This result is similar to that reported by Ramesh et al (2014) and Mumtaz et al(2017) in studies involving zinc solubilization by bacteria belonging to the genus Bacillus. In quantitative measurement, the isolates AP-JNFb-3-2, RHI-JMVL-3-1 and RHI-LGP-3-1, closely related to bacteria belonging to the genera Pseudomonas and Enterobacter, presented the greatest solubilization potential with zinc content in the media between 142.9 and 147.8 µg mL -1…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A total of 25 isolates from C. brasiliensis tissues and the rhizosphere presented ability to solubilize zinc in the qualitative test, of which eight presented halo diameters greater than or equal to 13 mm. This result is similar to that reported by Ramesh et al (2014) and Mumtaz et al(2017) in studies involving zinc solubilization by bacteria belonging to the genus Bacillus. In quantitative measurement, the isolates AP-JNFb-3-2, RHI-JMVL-3-1 and RHI-LGP-3-1, closely related to bacteria belonging to the genera Pseudomonas and Enterobacter, presented the greatest solubilization potential with zinc content in the media between 142.9 and 147.8 µg mL -1…”
Section: Discussionsupporting
confidence: 91%
“…. Mumtaz et al(2017) also reported higher IAA production by bacterial endophyte isolates from rice seeds (between 11.5 to 38.8 µg mL ), respectively. On other hand, Tsavkelova et al(2005aTsavkelova et al( , 2007b showed that the quantities of IAA secreted in the liquid culture by bacteria isolated from tropical orchids varied from 0.5 to 92.9 μg mL -1 .…”
Section: Discussionmentioning
confidence: 86%
“…Several previous studies also indicate an enhancement in different crop growth and yield inoculated with plant growth-promoting bacterial strains [33,48,[50][51][52][53][54]. Additionally, improved root growth, which enhanced the overall plant growth owing to the well-acquisition of water and nutrients from the soil have also resulted in better growth and yield of the plants.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, it is reported that ZSB alone and with organic matter is involved in the bio-activation of ZnO and enriched cereal grains with Zn [33]. In such a way, ZSB can be exploited to mobilize unavailable Zn and promote plant growth and yield through Zn assimilation [33,48,49]. In the present study, four BOZ formulations were produced by enriching the ZnO-orange peel waste composite with ZSB: Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn) is another micronutrient which is important for metabolic enzyme systems and optimal plant growth and development (Brown et al, 1993). Zn deficiency is well reported in soils around the world and is a commonly occurring problem in crop plants, leading to decreases in crop yield and nutritional quality (White and Zasoski, 1999;Mumtaz et al, 2017). Similar to P and Fe, Zn is also inaccessible to plants due to its low solubility where it is found in different forms in soil (e.g., Smithsonite/ZnCO 3 ) and its solubility is highly dependent on pH (higher solubility at low pH) (Martínez and Motto, 2000;Vodyanitskii, 2010).…”
Section: Plant Growth Promoting Traits and Potential For Growth Promomentioning
confidence: 99%